2023
DOI: 10.1111/1475-6773.14157
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider bias in the Appalachian region: The frequency and impact of contraceptive coercion

Abstract: Objective To investigate the frequency and impact of contraceptive coercion in the Appalachian region of the United States. Data Sources and Study Setting In fall 2019, we collected primary survey data with participants in the Appalachian region. Study Design We conducted an online survey including patient‐centered measures of contraceptive care and behavior. Data Collection/Extraction Methods We used social media advertisements to recruit Appalachians of reproductive age who were assigned female at birth (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In our online survey, participants responded to open- and closed-ended questions about their health and contraceptive care. Based on theoretical conceptualizations of upward and downward contraceptive coercion [ 11 , 15 ] and our previous research interviewing stakeholders about regional family planning needs [ 19 ], we developed the five-item Coercion in Contraceptive Care Checklist. Figure 1 displays the items measuring the targeted aspects of contraceptive coercion dichotomously (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our online survey, participants responded to open- and closed-ended questions about their health and contraceptive care. Based on theoretical conceptualizations of upward and downward contraceptive coercion [ 11 , 15 ] and our previous research interviewing stakeholders about regional family planning needs [ 19 ], we developed the five-item Coercion in Contraceptive Care Checklist. Figure 1 displays the items measuring the targeted aspects of contraceptive coercion dichotomously (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
“…For example, discouraging or refusing a wanted permanent contraception procedure, as documented in several studies [ 9 , 12 , 13 , 14 ], are examples of downward coercion. Conversely, upward coercion involves pressure from a healthcare provider to use contraception [ 11 , 15 ]. Forcible sterilization, as well as the promotion of or refusal to remove LARC methods, are examples of upward coercion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional evidence suggests people seeking contraception in Appalachia experience coercion related to their care. Swan et al [9] found that more than one-third of Appalachian women reported health care provider coercion related to their contraceptive method in a recent study, including both pressure to use and not use contraception.…”
Section: Introductionmentioning
confidence: 99%